Social media usage and behaviour among generation Y and Z in Malaysia - Dalol, Ahmed Azmi; Islam, Rafikul; Humayun, Kabir Sardar Md. (Inderscience Enterprises Ltd., 2021)
Abstract Social media is an important outlet for media agencies as they have wide reach and impressive targeting tools which conventional marketing lack. The main objective of the present research is to investigate the relationship between satisfaction through social media usage among Generation Y and Z in Malaysia and their five social needs, namely relationship, learning, recognition, diversion, and progression. The study employed a survey method whose sample was drawn from the youths in Malaysia. The survey questionnaire was distributed among the targeted group using a link through SurveyMonkey website. The questionnaire was pre-tested by two professors in the related field. Altogether 98 usable completed questionnaires were received. The study finds that satisfaction through the usage of social media among Generation Y and Z in Malaysia is significantly related with the users’ diversion and learning needs. The study also finds that the Generation Y and Z are fully dependent on smartphones for social media usage. Another finding is that 34% of the respondents spent more than 6 hours per day in using various social media. The work concludes that there is a need to promote more sensitive approaches in the social media marketing and to provide a passage for marketers to use while developing their marketing plans.